ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA : ( STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE TAHUN 2008-2011) - Amalina, Nur; Sabeni, Arifin (Diponegoro Journal of Accounting, 2014)
The rapid capital market development currently creates some opportunities and alternative for investor. On the other hand, the company should be compete to get fund from the investor. The Company can get some fund by raising and selling some stock to investor in capital market.Related with the problem that is raised , the purpose of this research is provide empirical evidence concerning the effect of Current Ratio (CR), Leverage Ratio (LR), Inventory Turnover (IT), Operating Profit Margin (OPM) and Price Earning Ratio (PER) in predict the earning changes in manufacture company for one next year period.Â The Object population of this research are manufacture company listed on BEI and reported in ICMD from 2008 to 2011, 25 company sample Â result by random sampling technique. Tools of data analysis used in this study is the classical assumption test, multiple regression analysis, hypothesis testing, and the coefficient of determination.Based on the result and study, it can generalized that there is significant effect between the Current Ratio (CR), Operating Profit Margin (OPM) to earning changes. Besides there is no significant effect between Leverage Ratio (LR), Inventory Turnover (IT) and Price Earning Ratio (PER) to earning changes.